Penggunaan Media Diorama Rantai Makanan Ekosistem Laut - Lativa Qurrotaini; Sila Dwi Kinanti; Sindy Kinanty Jelita; Shafa Zahara (Madako Elementary School, 2024)
The use of diorama media for marine ecosystem food chains in science learning is a support in achieving the success of learning objectives. This study was conducted to determine the function of dioramas in science learning. Kemmis and Mc Taggart's class-action research-based literature study model became this research method. The target subjects of this study involved 28 students in grade IV of SD Negeri Cireundeu 02 in the 2022/2023 school year. Many literatures have proven the effectiveness of diodrama media in improving students' understanding of science concepts in various material families. The effectiveness of the use of diodrama media is also proven after being applied in teaching the food chain of marine ecosystems in elementary school science, although it still has several weaknesses. Despite the weaknesses possessed, in terms of helping the development of students' understanding of science concepts is very helpful significantly, This can be seen from the student learning outcomes from meeting I as many as 78.57% (22 students) have achieved learning completion, and meeting II as many as 89.29% (25 students) who were declared successful. The results of this study certainly contribute effectively in eliminating student learning passivity and encouraging improvement in learning outcomes.